The Use of Classic Hallucinogens/Psychedelics in a Therapeutic Context: Healthcare Policy Opportunities and Challenges - dos Santos RG; Bouso JC; Rocha JM; Rossi GN; Hallak JE (Dove Medical Press, 2021)
Rafael Guimarães dos Santos,1– 3 José Carlos Bouso,1,3,4 Juliana Mendes Rocha,1 Giordano Novak Rossi,1 Jaime E Hallak1,2 1Department of Neurosciences and Behavior, Ribeirão Preto Medical School, University of São Paulo, Ribeirão Preto, Brazil; 2National Institute of Science and Technology – Translational Medicine, Ribeirão Preto, Brazil; 3ICEERS Foundation, International Center for Ethnobotanical Education, Research and Services, Barcelona, Spain; 4Medical Anthropology Research Center, Universitat Rovira i Virgili, Tarragona, SpainCorrespondence: Rafael Guimarães dos SantosDepartamento de Neurociências eCiências do Comportamento, Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo, Hospital das Clínicas, Terceiro Andar, Av. Bandeirantes, 3900, Ribeirão Preto, SP, BrazilEmail banisteria@gmail.comAbstract: Psychedelics or serotonergic hallucinogens are a group of substances that share the agonism of serotonergic 5-HT2A receptors as their main mechanism of action. Its main effects include changes in perception, cognitive process, and mood. Despite being used for centuries by different cultures in ritual contexts, these substances have currently aroused the interest of science and industry for their promising antidepressant, anxiolytic, and anti-addictive effects. Considering this evidence, this article aims to explore some of the possible health policy challenges to integrate these therapeutic tools into broad and heterogeneous health systems. As a main benefit, these substances produce rapid and enduring effects with the administration of single or few doses, which could lead to new treatment possibilities for patients with severe mental disorders resistant to the usual medications. The main challenge is associated with the fact that these substances remain scheduled in most countries and are associated with social stigma related to their recreational use (especially LSD and psilocybin). This situation makes it exceedingly difficult to conduct clinical trials, although international conventions allow such research. Ethically, this could be interpreted as a violation of human rights since thousands of people are prevented from having access to possible benefits. Interestingly, ritual ayahuasca use is more acceptable to the public than the use of psilocybin-containing mushrooms or LSD. The controlled, clinical use of LSD and psilocybin seems to be less criticized and is being explored by the industry. Rigorous scientific evidence coupled with industrial interests (LSD and psilocybin), together with respect for traditional uses (ayahuasca) and international conventions, seems to be the best way for these drugs to be integrated into health systems in the next years. Which highlights the need for an urgent dialogue between science, health system, society, and politics.Keywords: hallucinogens, psychedelics, healthcare